1993
DOI: 10.1111/j.1540-4560.1993.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity Ideology: Its Impact on Adolescent Males' Heterosexual Relationships

Abstract: This paper calls attention to the impact of masculinity ideology, an aspect of gender‐related attitudes, on adolescent males' heterosexual relationships. Previous approaches to the male gender role and close relationships, and attitudes toward the male gender role (the operationalization of masculinity ideology), are briefly reviewed. Data from the 1988 National Survey of Adolescent Males are reported. With sociodemographic and personal background factors controlled, males who hold traditional attitudes toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
325
2
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(352 citation statements)
references
References 35 publications
(31 reference statements)
13
325
2
12
Order By: Relevance
“…In HIV research, many discussions of masculinity have focused on the negative or risky implications of masculinity beliefs, which are frequently associated with high-risk behaviors such as sexual partner concurrency and inconsistent condom use. 36,38 Interestingly, one recent study found that having more male family network members and confidants was associated with lower HIV rates among YBMSM. 43 Therefore, although endorsement of traditional masculinity beliefs tends to increase risk, there may also be a necessary and risk-lowering aspect to masculine socialization, which many of our participants were missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HIV research, many discussions of masculinity have focused on the negative or risky implications of masculinity beliefs, which are frequently associated with high-risk behaviors such as sexual partner concurrency and inconsistent condom use. 36,38 Interestingly, one recent study found that having more male family network members and confidants was associated with lower HIV rates among YBMSM. 43 Therefore, although endorsement of traditional masculinity beliefs tends to increase risk, there may also be a necessary and risk-lowering aspect to masculine socialization, which many of our participants were missing.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Higher levels of agreement with traditional masculinity beliefs are generally associated with risk behaviors such as sexual partner concurrency and inconsistent condom use. [36][37][38] Some researchers have suggested that growing up with non-resident fathers is associated with less adherence to traditional masculinity norms, 39 which might be interpreted as portending lower sexual risk. On the other hand, other work in adult black MSM described lack of masculine socialization from absent biological fathers in childhood and adolescence as a potentially detrimental influence on partner selection and risky sex later in life.…”
Section: Masculine Socializationmentioning
confidence: 99%
“…And girls who report more sexual self-efficacydability to act on their sexual needsdare more likely to have used condoms at first intercourse (Impett, Schooler, & Tolman, 2006). Boys also need to be bolstered in their autonomy so they are better equipped to resist rigid masculinity norms, whichdlike rigid femininity normsdcan undermine contraceptive use and sexual health (Pleck, Sonenstein, & Ku, 1993).…”
mentioning
confidence: 99%
“…Increase the number of primary care settings that implement evidence-based alcohol screening and brief intervention SA- 13 Reduce past-month use of illicit substances SA- 14 Reduce the proportion of persons engaging in binge drinking of alcoholic beverages SA- 18 Reduce steroid use among adolescents Sexual and reproductive health FP-9 Increase the proportion of adolescents aged 17 yr and under who have never had sexual intercourse FP-9. 2 Increase the proportion of male adolescents aged 15 to 17 yr who have never had sexual intercourse FP-9.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Among adolescents and young adult males, masculine beliefs have not only been associated with poor sexual health outcomes, but also poorer mental health outcomes and lower levels of engagement with health services. [13][14][15][16] Thus masculinity has implications for both engaging young men in health care and for maximizing their health status.…”
Section: Masculinitymentioning
confidence: 99%